Restoration of bronze bushes by the method of surface plastic deformation - Shepelenko, I. V.; Warouma, Arifa; Cherkun, Vitalii; Черкун, Віталій Володимирович; Черкун, Виталий Владимирович (My University, 2016)
The restoration cost for agricultural machinery parts systematically influences on that of agricultural production. Hence the need to find the most effective and less expensive methods for repairing these parts. The bushes of the connecting rods of internal combustion engines are among the parts that wear out quickly and are made with expensive and deficient bronzes. The technical equipment used consists a worn out bushes of bronze treated by various methods, a vibro-rolling device, deformation software, a profilograph-profilometer, a microscope, and a machine of friction. In order to analyze the performance of the bushes of the connecting rods of internal combustion engines resulting from various treatments, the following parameters were determined: the height of the micro-relief elements, the absorption and the surface oil retention force, the optimum support surface, the wear and the wear intensity, the temperature of the friction area and the duration of the running-in period. The vibro-rolling followed by the deformation by broaching increases oil retention force from 1.8 to 2 times, and the wear resistance from 1.86 to 3.45 times as compared with the traditional technology. This new technology can be used for the restoration of the bushes of the connecting rods of internal combustion engines.
Keywords: Bushes; Vibro-Rolling; Reaming; Deforming Broaching; Wear